Assessment of Therapeutic Indications of Surgical Navigation in Maxillofacial Surgery: A Systematic Review and Meta-analysis - Marzieh Jamali; Javad Jamali; Marzieh Ghasemi Vojoodi; Hashem Ahmadizadeh (International Journal of Scientific Research in Dental and Medical Sciences (IJSRDMS), 2020)
Background and aim: Surgical navigation development and utilization in oral and maxilla-facial surgery quickly progressed in current years, and therapeutic indicators would be presented. The present systematic review and meta-analysis aimed at assessment of therapeutic indications of surgical navigation in maxillofacial surgery. Materials and methods: MEDLINE, PubMed, Cochrane Library, Embase, ISI, google scholar has been utilized as the electronic databases for performing systematic literature until 2010 to 2019. Therefore, Endnote X9, which is one of the software programs in the market, has been utilized to manage the titles electronically. Searches were performed with keywords, "Orthognathic surgery", "reconstruction surgery"," maxillofacial surgery"," Computer Assisted OR Computer methods", "navigation" "Maxillofacial Injuries", "Osteotomy, maxillary". The current systematic review has been conducted about the primary issue of the PRISMA Statement-Preferred Reporting Items for Systematic Reviews and Meta-analysis. Results: Heterogeneity found (I2 = 80.3%; P=0.000) and meta-analysis indicated a risk ratio of 0.187 (95% CI: 0.16- 0.21) (figure2). Surgical navigation could be considered a useful surgical tool. In orthognathic surgery, Heterogeneity found (I2 = 72.3%; P=0.006) and meta-analysis suggested a risk ratio of 0.10 (95% CI: 0.08-0.14). Finally, SN demonstrated to be a great tool to treat the diseases. Conclusion: This study indicated SN could be a beneficial device for each intended indication.